2009
DOI: 10.1161/circheartfailure.108.798389
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Renal Effects of the A1 Adenosine Receptor Antagonist SLV320 in Patients With Heart Failure

Abstract: Background-Blocking the tubuloglomerular feedback mechanism with adenosine A1 receptor antagonists seems to improve diuresis and sodium excretion without compromising the glomerular filtration rate in patients with heart failure. However, the direct cardiac effects of this compound class have not been investigated to date. Methods and Results-In total, 111 patients (109 men and 2 women) received a 1-hour infusion of 5, 10, and 15 mg SLV320, an adenosine A1 receptor antagonist, placebo, or 40 mg furosemide. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
4
23
2
Order By: Relevance
“…Finally, the authors present data with correction for multiple comparisons and consider significant unadjusted pair-wise comparisons only if the overall treatment effect is significant. This correct approach may explain the relatively neutral findings of this report in comparison with more optimistic renal data presented in the original abstract 10 and attests to the importance of peer and statistical review. In the current era of enhanced public oversight of medical research, unbiased peer review is particularly important to eliminate any perceived conflict of interest in a sponsor-initiated or -reported study or both.…”
Section: The Current Study In Contextsupporting
confidence: 65%
See 1 more Smart Citation
“…Finally, the authors present data with correction for multiple comparisons and consider significant unadjusted pair-wise comparisons only if the overall treatment effect is significant. This correct approach may explain the relatively neutral findings of this report in comparison with more optimistic renal data presented in the original abstract 10 and attests to the importance of peer and statistical review. In the current era of enhanced public oversight of medical research, unbiased peer review is particularly important to eliminate any perceived conflict of interest in a sponsor-initiated or -reported study or both.…”
Section: The Current Study In Contextsupporting
confidence: 65%
“…In this issue of Circulation: Heart Failure, Mitrovic et al 9 report the results of a phase II study with the selective adenosine A 1 receptor antagonist SLV320 in heart failure-a study that was carried out in 2005, first reported at a national meeting in 2008, 10 and appears now after peer review. To determine the cardiorenal effects of adenosine receptor blockade, investigators randomly assigned 111 patients with chronic systolic heart failure and edema despite loop diuretic therapy to receive a 1-hour infusion of SLV320 (5, 10, or 15 mg), furosemide 40 mg, or placebo.…”
Section: The Current Study In Contextmentioning
confidence: 99%
“…It would be of interest to analyze potential effects of linagliptin in non-diabetic models of chronic renal failure as well, since the observed effects were independent of the glucose lowering effects of linagliptin. Moreover, our findings should stimulate investigators to perform clinical studies using either suitable biomarker strategies for phase 2 studies [53][54][55][56] or hard clinical endpoints typically used in phase 3 registration trails for chronic renal failure such as doubling of serum creatinine, need for renal replacement therapy and total mortality [57] investigation the effects of linagliptin in patients with diabetic nephropathy.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,4,5,22,23 As a result, there has been considerable interest in A 1 -receptor antagonists, which have enhanced the response to diuretics in patients with heart failure, usually without further deterioration of renal function. [7][8][9][10][23][24][25] With the use of a protocol that was similar to that in the present trial, the PROTECT pilot study randomly assigned 301 patients with acute heart failure to placebo or to 10-, 20-, or 30-mg doses of rolofylline. 11 In the pilot trial, the group of patients who received 30 mg of rolofylline were more likely than those who received placebo to have improvement in dyspnea on days 2 and 3 (59.4% of patients vs. 41.3%) and were less likely to have persistent renal impairment (8.0% vs. 18.2%), with a trend toward a lower 60-day rate of death or readmission for cardiovascular or renal causes (19% vs. 34%; hazard ratio, 0.55; 95% CI, 0.28 to 1.04; P = 0.06).…”
Section: Discussionmentioning
confidence: 99%